(untitled) (Cadernos de Psicologia Social do Trabalho, 2011)
Traffic accident kills each year over 30,000 people within Brazil. Part of these involves workers in working situation, although there are few studies interested in these issues. Researchers focusing aspects of the way of conduction, as the body use in the piloting process, are even less frequents. Through researches operated by ergological perspective, we verified that the urban piloting process excels by though, intelligence, cognition and the way they articulate to a biological, psychical, cultural and historical body: a body-self. The impossibility of a complete traffic condition prescription, since it requires the intelligence of practice, imposes the use of this concept. Piloting involves an entire body mobilization, developing knowledge and experience that assist task performance and facing traffic activity constraint. Thus, the recognition of this body-self becomes a fundamental key for understanding the professional conductor's behaviors.